Imaginário e memória do patrimônio histórico edificado de Goiânia: mudanças e permanências da fundação aos dias atuais - Soares , Sueli Souza de Oliveira (2024)
“Imagination and Memory of the built historical heritage of Goiânia: changes and permanence from the foundation to the present day” is the result of an accurate exercise of looking at the city in search of symbols, meanings, values and representations present in urban images. We outline our reflections around the reading of the built historical heritage from two different points of view, from the perspective of current views and from the perspective of historical views. In reading the heritage from these different perspectives in different temporalities, we grasp the meanings through fragments of the city, monuments and places of memory, we observe the imaginary, the desires and the feelings influenced by personal trajectories. In this exercise, we find that the built historical heritage establishes itself as one of the anchors of the representation of Goiânia, capable of engendering a relationship between imagination and memory. We built this trajectory in order to meet the main challenge of this thesis, which is to investigate the interface between the historical built heritage of Goiânia (GO) and the imaginary of modernity constructed in the early days of the city founded in 1933. The approach to the theme is multidisciplinary, in an interface zone between Humanist Geography, History and Architecture and Urbanism, in light of the imaginary of the city. The work seeks an innovation from a methodological point of view, which has at its core the subject-object relationship, based on the perception of the city. On the one hand, it is in tune with the theoretical approach that points out paradigms on theories of the urban imaginary and, on the other, it proposes an approach to the theme of urban memory, based on the reading of the historical built heritage of Goiânia, where not only the building, its forms and characteristics of its architectural style will be read.